Basic directions activity of management organs providing non-olympic sports in Ukraine - Долбишева [Dolbysheva N.], Ніна Григоріївна; Саварец [Savarets E.], Є. Ю. (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--> The article is the management structure non-Olympic sports in Ukraine at the level of the state central authorities and public organizations. A summary of the problem, the direction of the Ministry of Education and Science, Youth and Sport, and Sport Committee of Ukraine, which provide financial support for the development and non-Olympic sports. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->